The Art and Science of Evaluating Online Programs - Mary-Katherine Smith; Kathy Adler (Academic Chairpersons Conference Proceedings, 2017)
Evaluation of online programs is an elusive blend of art and science. The science is based on a mix of technological opportunities and research techniques. This session explores innovative practices in evaluation of online higher education and how the results can be used to guide the growth of a program.
Keywords: Technology Qualitative Quantitative Online Evaluation